2016
DOI: 10.1128/jcm.03050-15
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Human DNA in Spiked Clinical Specimens for Improvement of Sensitivity of Pathogen Detection by Next-Generation Sequencing

Abstract: Next-generation sequencing (NGS) technology has shown promise for the detection of human pathogens from clinical samples. However, one of the major obstacles to the use of NGS in diagnostic microbiology is the low ratio of pathogen DNA to human DNA in most clinical specimens. In this study, we aimed to develop a specimen-processing protocol to remove human DNA and enrich specimens for bacterial and viral DNA for shotgun metagenomic sequencing. Cerebrospinal fluid (CSF) and nasopharyngeal aspirate (NPA) specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
164
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(175 citation statements)
references
References 27 publications
(24 reference statements)
10
164
0
1
Order By: Relevance
“…Additionally, previous studies using the MolYsis kit focused on improving techniques such as real-time PCR, whereas use of these methods for WGS, where microbial DNA enrichment could be even more useful, has been less studied (Votintseva et al, 2015). Other methods such as host cell lysis with detergents (Hasan et al, 2016) or ox bile (Zhou & Pollard, 2012) and immunoprecipitation of DNA with inactive methyl-specific restriction endonucleases (Barnes et al, 2014; Liu et al, 2016) have also been reported, but are not available as commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies using the MolYsis kit focused on improving techniques such as real-time PCR, whereas use of these methods for WGS, where microbial DNA enrichment could be even more useful, has been less studied (Votintseva et al, 2015). Other methods such as host cell lysis with detergents (Hasan et al, 2016) or ox bile (Zhou & Pollard, 2012) and immunoprecipitation of DNA with inactive methyl-specific restriction endonucleases (Barnes et al, 2014; Liu et al, 2016) have also been reported, but are not available as commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach for pathogen enrichment in mNGS libraries is the use of a host depletion method. Such methods include differential lysis 37 , the removal of abundant human ribosomal and mitochondrial RNA sequences using antibody hybridization or depletion of abundant sequences by hybridization (DASH) 38 and nuclease treatment before extraction 39,40 . Aside from a post-extraction DNase step, we did not incorporate host depletion as part of MSSPE, given that these methods can be cumbersome, with additional Abbott m2000 RT-PCR assays were used to estimate the titres of HIV and HCV; viral titres for other viruses were estimated using in-house qRT-PCR assays with standard curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…d Absolute percentage increase from using random primer only (coverage by SP (%) − coverage by RH (%)); coverage of 40-60% is sufficient for genotypic and phylogenetic inference from partial genome assemblies 27 steps, and difficult to standardize. Furthermore, host depletion methods can bias detection towards specific pathogen types, such as the enrichment of bacteria and fungi with cell walls with differential lysis 37 , or encapsidated viruses with pre-extraction nuclease treatment 39,40 . Host depletion can also be performed at the RNA level by the use of non-human primers to bias against abundant human host ribosomal and/or mitochondrial RNA 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study has initiated the optimization of several steps throughout the presequencing and postsequencing workflow, which are considered essential for sensitive and specific mNGS-based virus detection. Many virus discovery or virus diagnostic protocols have focused on the enrichment of viral particles 32 with the intention to increase the relative amount of virus reads. However, these methods are laborious and intrinsically exclude viral nucleic acid located in host cells.…”
Section: Discussionmentioning
confidence: 99%